Efeito de diferentes solventes nas propriedades fotoluminescentes do CaMoO4 - Botelho, Gleice Lorena Gonçalves Tavares (Universidade Federal de São Carlos, 2013)
The CaMoO4 has been extensively studied due to its luminescent emissions in the visible region of the electromagnetic spectrum at room temperature, presenting potential for technological applications including lasers, light emitting diodes and lamps. The solvent and the method utilized in the synthesis are important in the control of the obtained powders morphology. Therefore, in this master s thesis CaMoO4 samples were obtained by microwave-assisted solvothermal and coprecipitation method, using ethylene glycol and 1,3-propanediol as solvent. As experimental results, the X-ray diffraction patterns and Infrared and Raman-active vibration modes proved that all powders have a scheelita-type tetragonal structure. The Rietveld refinements suggested the existence of distortion both [MoO4] and [CaO8] clusters. The ultraviolet-visible absorption spectra indicated the presence of intermediary energy levels within the band gap, which are arising from structural defects in the materials. Field-emission gun scanning electron microscopy and transmission electron microscopy images revealed the obtainment of nanoscale and agglomerated particles. When excited with 350 nm wavelength, all samples exhibited broadband photoluminescence emissions in the region of the blue and/or green of the electromagnetic spectrum.
Effect of different solvents in the photoluminescent properties of CAMOO4
Keywords: Físico-química; Propriedade fotoluminescente; Molibdato de cálcio; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA